2021
DOI: 10.1111/ddi.13286
|View full text |Cite
|
Sign up to set email alerts
|

Exploring ecological specialization in pipefish using genomic, morphometric and ecological evidence

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 82 publications
(134 reference statements)
0
3
1
Order By: Relevance
“…In addition, previous studies showed that morphological adaptation to local ecology can also have resulted from phenotypic plasticity or from genetic differences among populations (Borokini et al, 2021;Ghalambor et al, 2007;Kunz et al, 2022;Price et al, 2003;Schmid & Guillaume, 2017). Although phenotypic plasticity has been documented in response to variations in multiple environmental variables (Chevin & Lande, 2015;Gratani, 2014;Lande, 2009;Wang et al, 2021), we found morphological distance was not correlated with environmental distance after controlling for geographic distance (Table 6). Thus, environmental factors are unlikely to be responsible for the observed morphological differentiation in P. kawadai.…”
Section: Factors Affecting Morphological Differences Among Platycerus...contrasting
confidence: 57%
“…In addition, previous studies showed that morphological adaptation to local ecology can also have resulted from phenotypic plasticity or from genetic differences among populations (Borokini et al, 2021;Ghalambor et al, 2007;Kunz et al, 2022;Price et al, 2003;Schmid & Guillaume, 2017). Although phenotypic plasticity has been documented in response to variations in multiple environmental variables (Chevin & Lande, 2015;Gratani, 2014;Lande, 2009;Wang et al, 2021), we found morphological distance was not correlated with environmental distance after controlling for geographic distance (Table 6). Thus, environmental factors are unlikely to be responsible for the observed morphological differentiation in P. kawadai.…”
Section: Factors Affecting Morphological Differences Among Platycerus...contrasting
confidence: 57%
“…Indeed, SDMs generally assume uniformity of responses to climate, ignoring local adaptations and intraspecific variations (Franken et al, 2018;Hereford, 2009;Wang et al, 2021;Zhang et al, 2021).…”
Section: Linking Genetic Data and Distributionsmentioning
confidence: 99%
“…Rapid developments in statistical analysis and phylogeny have resulted in more biodiversity indicators based on PD being proposed, including calculations of endemic species diversity patterns such as weighted (Crisp et al., 2001) and phylogenetic endemism (Rosauer et al., 2009). The study of niches also contributes to an improved understanding of the distribution patterns of species and those environmental factors that affect them (Rödder et al., 2017; Wang et al., 2021; Zheng et al., 2021).…”
Section: Introductionmentioning
confidence: 99%